BMT MERUPAKAN LEADING SECTOR UNTUK PEMBIAYAAN USAHA MIKRO - Lasmiatun - (DHARMA EKONOMI, 2012)
BMT is one of the micro economy organization which focused for increasing the exertion quality and member prosperity in particular and its society in general by menas of giving the financial capital loan. BMT plays role and function in some cases for reaching that goal : The first, identified, mobilized, organized, motivated, and developed the economic potency of member and muamalat member group in its region of occupation. The second, raised the quality of member human resources for being more professional and “islami” with the result that more and more intact and strong in facing the global rivalry. The thirth, supported and mobilized the public potency for raising the member prosperity, except that, also could give the added value for member and society. The fourth, be a financial mediator between agniya’ as shohibul maal and dhu’afa as mudharub, especially for social donation like zakat, infaq, shodaqoh, wakaf, hibah and etc. BMT, in this case, as a amil who asking it and furthermore, it would be distributed again for the group of society in case of need. The fifth, be a financial mediator between fund owner, as a financier and depositor with fund user for developing productive effort.Keywords:BMT.